Possible influences of pacific decadal oscillation in the ten day based radio between actual and potential evapotranspiration in the region of Campinas, São Paulo State, Brazil - Blain,Gabriel Constantino (2009)
Considering the importance of the ratio between the actual and potential evapotranspiration (AE/PE) for agricultural purposes, the present study estimated the 10-day based AE/PE, aiming to evaluate possible influences of the Pacific Decadal Oscillation (PDO), on temporal variability series, in the region of Campinas, São Paulo State, Brazil. The shapes of the beta probability density function of the AE/PE series for four periods (two in the cold PDO phase and two in the warm PDO phase) do not show differences between the PDO phases. In this sense, the use of "average periods" to obtain a standard climatology for agrometeorological purposes (such as the climate normal of the 1961-1990 period, which encompasses sixteen years of the cold PDO phase and fourteen years of the warm PDO phase) should not result in significant errors in the region of Campinas, SP. However, considering academic/scientific purposes, the analyses of the autocorrelation functions of the residual AE/PE series for the four periods show differences in the persistence between the two phases of the PDO.